La alucinante historia de Juanito Tot y Verónica Flut : (los niños que intentaron batir todos los records) - Barba, Andrés, 1975-; Vivas, Rafa (Madrid : Ediciones Siruela, 2015)
Two friends, Juanito Tot and Verónica Flut, respond to an ad by Klaus Wintermorgen to set a world record in 30 days which the invincible Klaus cannot break.
Online resource; title from ePub title page (Digitalia, viewed April 10, 2017)
Keywords: World records -- Fiction; Friendship -- Fiction; Electronic books